Knockdown of a mucin‐like gene in Meloidogyne incognita (Nematoda) decreases attachment of endospores of Pasteuria penetrans to the infective juveniles and reduces nematode fecundity. (22nd October 2018) - Phani, Victor; Shivakumara, Tagginahalli N.; Davies, Keith G; Rao, Uma
Summary: Mucins are highly glycosylated polypeptides involved in many host–parasite interactions, but their function in plant‐parasitic nematodes is still unknown. In this study, a mucin‐like gene was cloned from Meloidogyne incognita ( Mi‐muc‐1, 1125 bp) and characterized. The protein was found to be rich in serine and threonine with numerous O ‐glycosylation sites in the sequence. Quantitative real‐time polymerase chain reaction (qRT‐PCR) showed the highest expression in the adult female and in situ hybridization revealed the localization of Mi‐muc‐1 mRNA expression in the tail area in the region of the phasmid. Knockdown of Mi‐muc‐1 revealed a dual role: (1) immunologically, there was a significant decrease in attachment of Pasteuria penetrans endospores and a reduction in binding assays with human red blood cells (RBCs), suggesting that Mi‐MUC‐1 is a glycoprotein present on the surface coat of infective second‐stage juveniles (J2s) and is involved in cellular adhesion to the cuticle of infective J2s; pretreatment of J2s with different carbohydrates indicated that the RBCs bind to J2 cuticle receptors different from those involved in the interaction of Pasteuria endospores with Mi‐MUC‐1; (2) the long‐term effect of RNA interference (RNAi)‐mediated knockdown of Mi‐muc‐1 led to a significant reduction in nematode fecundity, suggesting a possible function for this mucin as a mediator in the interaction between the nematode and the host plant.